2020
DOI: 10.1371/journal.pone.0241469
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity evaluation of 2019 novel coronavirus (SARS-CoV-2) RT-PCR detection kits and strategy to reduce false negative

Abstract: The early detection and differential diagnosis of respiratory infections increase the chances for successful control of COVID-19 disease. The nucleic acid RT-PCR test is regarded as the current standard for molecular diagnosis. However, the maximal specificity confirmation target ORF1ab gene is considered to be less sensitive than other targets in clinical application. In addition, recent evidence indicated that the initial missed diagnosis of asymptomatic patients with SARS-CoV-2 and discharged patients with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 43 publications
(51 reference statements)
3
47
0
1
Order By: Relevance
“…As mentioned earlier, this is the reason why the occurrence of false negative results in context of ongoing epidemics should be taken cautiously. Evidence from Europe on the occurrence of false negative results for N-gene based assays support our in-silico findings [39,40]. Despite no present evidence on false negative results for RdRp gene based assays, its inherent mutation rate (due to environmental pressure and its role as a virulence factor) and having account this gene showed low sensitivity [41] is an aspect that deserves further investigation…”
Section: Discussionsupporting
confidence: 68%
“…As mentioned earlier, this is the reason why the occurrence of false negative results in context of ongoing epidemics should be taken cautiously. Evidence from Europe on the occurrence of false negative results for N-gene based assays support our in-silico findings [39,40]. Despite no present evidence on false negative results for RdRp gene based assays, its inherent mutation rate (due to environmental pressure and its role as a virulence factor) and having account this gene showed low sensitivity [41] is an aspect that deserves further investigation…”
Section: Discussionsupporting
confidence: 68%
“…Second, different probes and primer targets result in different amplification efficiencies and Ct values. 36,37 It is known that PCR amplification efficiencies critically influence the Ct values; for example, the number of viral genome copies estimated by a Ct value of 37 in PCR with an amplification efficiency of 100% is equal to that estimated by a Ct value of about 40 in PCR with an amplification efficiency of 90%. Each local laboratory in charge of diagnostic RT-qPCR testing should be aware of these differences when optimizing standard operating procedures and of the importance of regular laboratory quality checks and controls.…”
Section: Limitations Of Diagnosing Covid-19 Using Rt-qpcrmentioning
confidence: 99%
“…In China, Orf1ab and N genes are regularly used, while N1, N2 and N3 genes were utilized in US CDC and E, N, and RdRP genes in Europe [32]. The importance of N1 and N2 primer-probes is for providing a less conservative but more sensitive than the RdRP-SARSr primer-probes especially in samples that have low viral titers [33,34]. In a recent study, where swabs from con rmed cases were taken from nasopharynx and pharynx targeting ORF1ab and N genes yielded the best sensitivity when compared to positive con rmed samples [34].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of N1 and N2 primer-probes is for providing a less conservative but more sensitive than the RdRP-SARSr primer-probes especially in samples that have low viral titers [33,34]. In a recent study, where swabs from con rmed cases were taken from nasopharynx and pharynx targeting ORF1ab and N genes yielded the best sensitivity when compared to positive con rmed samples [34]. Chu et al [35] have reported two assays that had the capability to achieve a large dynamic range and recommended targeting N gene for screening and the ORF1b gene to con rm the result.…”
Section: Discussionmentioning
confidence: 99%